(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Strategic planning in management is the process of documenting and establishing a direction of your small business-by assessing both where you are and where you’re going. Strategy includes processes of formulation and implementation; strategic planning helps coordinate both. However, strategic planning is analytical in nature (i.e., it involves "finding the dots"); strategy formation itself involves synthesis (i.e., "connecting the dots") strategic thinking. As such, strategic planning occurs around the strategy formation activity.